Antioxidant analysis of Artocarpus heterophyllus drink. Issue 1 (April 2021) - Devi, M; Sunaryo, NA; Mansoor, AH
Abstract: Jackfruit leaves herbal drink is a functional beverage that contains a high antioxidant value. The addition of cinnamon and clove could improve the colour and aroma of jackfruit leaves herbal drink. The utilization of jackfruit leaves in herbal tea product is helpful to upgrade the usability of jackfruit leaves. This research aims to know the antioxidant capacity and antioxidant content (phenolics, flavonoids, tannins, saponins, gallic acid, kaempferol and quercetin) from 0.50%, 1% and 1.50% of jackfruit leaves. Herbal drink with the lowest hedonic score is 1 and the highest is 5. This research is including experiment research using Completely Random Design (CRD) with three kinds of treatment. The analyzed data using One Way ANOVA, if the treatments show a significant difference, then the analyzed data should be proceeded by Duncans Multiple Range Test with 5% confidence interval. The result is, the highest value of antioxidant capacity content (80.00 ppm), phenolics antioxidant (411.90 mg/l), flavonoids antioxidant (321.84 mg/l), tannin antioxidant (30.28 mg/l) saponin antioxidant (1.00 mg/l), gallic acid antioxidant (75.25 microgram/g), kaempferol antioxidant (22.38 microgram/g), quercetin antioxidant (32.33 microgram/g) in 1, 5% Artocarpus heterophyllus drink. Base on the result, it can be concluded that the jackfruit leaves herbal drink product proven as a functional drink which contains a high antioxidant value.